Hot corrosion studies in coal fired boiler environment - Kamal, S. (EDP Sciences, 2014)
Hot corrosion behaviour of the bare and D-gun coated superfer 800H exposed to low temperature super-heater zone of the coal fired boiler of Guru Nanak Dev Thermal Power Plant, Bathinda, Punjab, India. The specimens were hanged in the platen super-heater of coal fired boiler where the gas temperature was around 900 °C ±10 °C. Hot corrosion experiments were performed for 10 cycles, each cycle consisting of 100 hours exposure followed by 1 hour cooling at ambient temperature. Weight change measurements were done at the end of each cycle. The weight change data used for predicting hot corrosion behaviour of the coated alloys after the total exposure of 1000 hours. The different phases and their distribution in the hot corroded specimens were analysed with the help of FE-SEM/EDS and X-ray mapping. © 2014 Owned by the authors, published by EDP Sciences.